PENGARUH PENDIDIKAN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. RANCANG BANGUN NUSARAYA DI BANDAR LAMPUNG - Ahiruddin - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
The role of the human resource management is very important in realizing and help achievethe goals of the organization. One important element in the achievement of organizational goals isthe educational background and training programs to support the implementation of a program ofwork.The purpose of this research is wishing to know and analyze whether there is the influenceof education and job training either partially or simultaneously on the employee performance CV.Rancang Bangun Nusaraya. Object of this study were employees of CV. Rancang Bangun Nusarayatotaling 20 people by using the research method of explanation.Results showed a significant difference between education (X1) and Performance (Y), with Rsquare of 0.221 or 22.1%, which means that education contributes to the performance by 22.1%. Inother words, there was 77.9% is determined by other factors. A significant difference between theJob Training (X2) with Performance (Y), with R square of 0.214 or 21.4%, which means that the JobTraining (X2) accounted for 21.4% contribution to the performance. In other words, there was 78.6%is determined by other factors. There is a significant relationship between education (X1) and JobTraining (X2) on the Performance (Y), with R square of 0.297 or 29.7%, which means that theEducation and Job Training same shared affect the performance of 29.7%. In other words, there was70.3% is determined by other factors.